The Directive politeness in the tausiah of ustaz Adi Hidayat - Nuryasin, Mohammad; Martutik (Universitas Muhammadiyah Malang, 2024)
The purpose of this study is to describe (1) the form of directive speech and (2) speech action strategies in the framework of politeness in the language of Ustaz Adi Hidayat. This research is qualitative with a pragmatic approach. The method used is descriptive analysis. The form of data in this study is words, phrases, clauses, sentences, and paragraphs that represent the form of directive speech and speech action strategies. The data collection technique uses the look and note technique. The data in this study was analyzed using three steps, namely (1) reducing the data, (2) presenting the data, and (3) drawing conclusions. The results of this study are (1) the form of directive speech in the form of (a) the act of commanding is marked by the words please, pay attention, and come on; (b) the act of prohibition is marked by the word don't; (c) the demanding act is marked by the word must; and (d) the act of begging is marked by the word beg with polite language at a polite level and (2) the strategy of speech action in the form of (a) the strategy of positive politeness/familiarity is marked by sentences that contain jokes, (b) without strategies is marked by sentences that contain ridicule, and (c) indirect or disguised strategies are marked by sentences that contain sarcasm. The act of directive speech in Ustaz Adi Hidayat's tausiah tends to use a form of ruling with a positive politeness strategy in the form of jokes. The use of directive speech accompanied by jokes can provide a polite feel. The nuances of manners in the context of language can be an important factor so that information can be well received by speaking partners. This research contributes to the study of pragmatic, language politeness that can have theoretical implications in the realm of public speaking such as lectures and speeches, as well as in the context of learning.